Polska adaptacja skali Knee Outcome Survey Activities of Daily Living (KOS- ADL) - Szczepanik, Magdalena (Uniwersytet Rzeszowski, 2017)
Wstęp: Większość kwestionariuszy subiektywnej oceny zdrowia powstała w krajach anglojęzycznych, dlatego wykorzystanie ich w innych krajach lub społecznościach, nakłada na badaczy obowiązek adaptacji kulturowo-językowych. Jedną ze skal subiektywnej oceny stanu zdrowia pacjentów z różnymi dysfunkcjami stawu kolanowego, w tym ze zmianami zwyrodnieniowymi jest skala Knee Outcome Survey Activieties of Daily Living (KOS-ADL). Składa się ona z 14 pytań dotyczących stopnia nasilenia objawów ze strony stawu kolanowego oraz określenia trudności w codziennych czynnościach. Cel pracy: Celem pracy była polska adaptacja kulturowo-językowa skali KOS-ADL oraz weryfikacja jej powtarzalności, trafności i wrażliwości na zmiany kliniczne w subiektywnej ocenie stanu zdrowia pacjentów poddanych endoprotezoplastyce stawu kolanowego. Materiał i metoda: Zbadano 70 pacjentów (59 kobiet i 11 mężczyzn,średnia wieku 66lat) zakwalifikowanych do zabiegu endoprotezoplastyki stawu kolanowego. W celu adaptacji skali KOS-ADL wykorzystano: skalę KOOS i VAS, test TUG, 5xSTS oraz 10-cio metrowy test chodu. Badania przeprowadzono trzykrotnie: badanie pierwsze – tydzień lub dwa tygodnie przed zabiegiem operacyjnym (zebranie wywiadu, wypełnienie wszystkich skal i wykonanie wszystkich testów). Badanie drugie - 6 do 13 dni od pierwszego badania (wypełnienie skali KOS-ADL; test retest). Badanie trzecie - 6 miesięcy po zabiegu operacyjnym (analogiczne do badania pierwszego). Wyniki: W badaniach wykazano wysoką powtarzalność pomiarów KOS-ADL oraz dobrą zgodnością wewnętrzną. Stwierdzono przeciętne oraz średnie korelacje wyników z badania 1 pomiędzy KOS-ADL a skalą VAS, testami TUG oraz 5xSTS. Wykryto zależności pomiędzy wynikami w KOS-ADL a wynikami w KOOS. W celu określenia wrażliwości KOS-ADL wyliczono wartość ES. Zmiany wyników testów TUG, 5×STS oraz testu chodu nie były w statystycznie istotny sposób skorelowane z poprawą w skali KOS-ADL. Istotne statystycznie korelacje wystąpiły pomiędzy zmianą poziomu w skali VAS a zmianami w KOS-ADL. Wykazano znamienne statystycznie korelacje pomiędzy zmianami w KOS-ADL a zmianami w KOOS. Wnioski: Polska wersja skali KOS-ADL jest powtarzalnym, czułym oraz trafnym narzędziem w subiektywnej ocenie stanu zdrowia pacjentów poddanych endoprotezoplastyce stawu kolanowego.

Introduction: As the majority of subjective patient’s health scales origin from English spoken countries, usage of those in other countries and communities require performing of cultural and lexical adaptation. One of such, is Knee Outcome Survey Activieties of Daily Living Scale (KOS-ADL), used for evaluation of overall health of the patient with various dysfunctions of knee including osteoarthritis. It contains 14 questions, concerning the level of dysfunction of knee joint and defining difficulties in daily actions. Objective: The purpose of the thesis was cross-cultural adaptation of Polish version of KOS-ADL as well as verification of its reproducibility, validity and responsiveness to clinical changes in subjective evaluation of patient's overall health after knee replacement. Material and methods: The study group consisted of 70 patients (59 females and 11 males, average age of 66 years) qualified for knee replacement procedure. To adapt KOS-ADL scale the following scales and reference tests were applied: KOOS and VAS scales, TUG test, 5xSTS and 10 meters long gait test. The researches were conducted three times: first examination – one to two weeks prior to surgery (general interview, conducting all the tests and surveys), second examination – 6 to 13 days after the first survey (filling the KOS-ADL; test-retest), third examination – 6 months after the surgery (similarly to the first examination). Results: The surveys showed high repeatability of KOS-ALD results and good internal consistency. There were average and medium correlations found between KOS-ADL and VAS scales in the first examination, TUG tests and 5xSTS. There were dependencies observed between the results obtained in KOS-ADL and KOOS scales. There was ES value calculated in order to define the responsiveness of KOS-ADL. Differences in the results of TUG, 5xSTS and gait tests were not significantly correlated with the improvement of KOS-ADL scale. There were statistically significant correlations between the changes in VAS scale and improvement in KOS-ADL observed. Significant statistical correlations were shown between the changes in KOS-ADL and changes in KOOS. Conclusions: Polish version of KOS-ADL scale is a repeatable, responsive and valid tool in subjective evaluation of health of patients undergoing knee replacement surgery.
Polish adaptation of Knee Outcome Survey Activities of Daily Living Scale (KOS- ADLS)
Keywords: choroba zwyrodnieniowa stawu kolanowego; subiektywna ocena zdrowia; adaptacja skali; Osteoarthritis of the knee; subjective assessment of Health; adaptation of the scale